2006
DOI: 10.1007/s11207-006-2065-2
|View full text |Cite
|
Sign up to set email alerts
|

The Deceleration of an Interplanetary Transient from the Sun to 5 Au

Abstract: A CME which was first seen in LASCO is tracked through SMEI and on out to Ulysses. These measurements allow us to determine the deceleration and compare different models of the deceleration process. It is found that both a simple "snow plough" model and an aerodynamic drag model predict a much more rapid deceleration in the lower solar wind than is observed. Therefore some driving force is needed over an extended range of distances to account for the motion of the transient. It is conjectured that at least par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 22 publications
4
94
0
Order By: Relevance
“…Th is early phase is generally attributed to the Lorentz force whereby the dominant outward magnetic pressure overcomes the internal and / or external magnetic fi eld tension. Th e subsequent increase in velocity, at heights above ~ 7 R for this event, is predicted by theory to result from the eff ects of drag 17 , as the CME is infl uenced by solar wind fl ows of ~ 550 km s − 1 emanating from latitudes տ ± 5 ° of the ecliptic (again from inspection of the Wang-Sheeley-Arge model). At large distances from the Sun, during this postulated drag-dominated epoch of CME propagation, the equation of motion can be cast in the following form:…”
Section: Cme Observation On 12 December 2008mentioning
confidence: 74%
See 1 more Smart Citation
“…Th is early phase is generally attributed to the Lorentz force whereby the dominant outward magnetic pressure overcomes the internal and / or external magnetic fi eld tension. Th e subsequent increase in velocity, at heights above ~ 7 R for this event, is predicted by theory to result from the eff ects of drag 17 , as the CME is infl uenced by solar wind fl ows of ~ 550 km s − 1 emanating from latitudes տ ± 5 ° of the ecliptic (again from inspection of the Wang-Sheeley-Arge model). At large distances from the Sun, during this postulated drag-dominated epoch of CME propagation, the equation of motion can be cast in the following form:…”
Section: Cme Observation On 12 December 2008mentioning
confidence: 74%
“…Studies that compare in situ CME velocity measurements with initial eruption speeds through the corona show that slow CMEs are accelerated towards the speed of the solar wind, and fast CMEs decelerated 15,16 . It has been suggested that this is due to the eff ects of drag on the CME in the solar wind 17,18 . However, the quanti fi cation of drag, along with that of both CME expansion and non-radial motion, is currently lacking, primarily because of the limits of observations from single fi xed viewpoints with restricted fi elds of view.…”
mentioning
confidence: 99%
“…The cause of the increasing mass of the CME is generally accepted as solar wind material that is acreted ahead of the CME driver (its flux rope) as it expands through the heliosphere (e.g., Lugaz et al 2005;Tappin 2006;Howard et al 2007;DeForest et al 2013), as the CME measurements, including those made in the present study, typically include the so-called "sheath" component. This is evidenced by the substantial increase in the density of just the flank of the CME shown in Figure 2.…”
Section: Discussionmentioning
confidence: 95%
“…Gopalswamy et al 2000Gopalswamy et al , 2001Vršnak & Gopalswamy 2002;Yashiro et al 2004;Tappin 2006;Manoharan 2006;Vršnak & Žic 2007;Vršnak et al 2008). Taking into account the physical properties of the drag (e.g.…”
Section: Introductionmentioning
confidence: 99%